Performing Intimacies with Hawthorne, Austen, Wharton, and George Eliot A Microsocial Approach - Wakana, Maya Higashi (Springer International Publishing, 2018)
Performing Intimacies with Hawthorne, Austen, Wharton, and George Eliot analyzes literary reproductions of everyday intimacies through a microsociological lens to demonstrate the value of reading microsocially. The text investigates the interplay between author, character, and reader and considers such concepts as face and moments of embarrassment to emphasize how art and life are inseparable. Drawing on narrative theory, the phenomenological approach, and macro approaches, Maya Higashi Wakana examines Hawthorne's "The Minister's Black Veil," Austen's Pride and Prejudice, Wharton's Ethan Frome and The Age of Innocence, and George Eliot's The Mill on the Floss. Through a multidisciplinary approach, this book provides new ways of reading the everyday in literature. .